Developmental psychology : revisiting the classic studies - Slater, Alan.; Quinn, Paul C. (London ; Thousand Oaks, Calif. : SAGE, 2012)
This book revisits classic studies in Developmental Psychology with a view to showing not only how they shaped the field, but also how the field has itself moved on through engagement with the issues these studies raise. It engages critically with the studies in order to reveal new ways of thinking both about them and about the ideas they explore. In effect, it shows how Developmental Psychology can be - and has been - taken forward in exciting ways through a careful re-examination of the core studies that lie at its heart. The volume's chapters are written by internationally renowned scholars who are working at the cutting edge of the areas mapped out by particular classic studies and whose work has been heavily influenced by a deep appreciation of the research that they write about. As a result, the chapters give readers profound insights into the foundations of Developmental Psychology, but also show how the discipline has advanced in important ways in the years since those studies were conducted. Written in an accessible and engaging style, each chapter uses a similar structure to explore a particular classic study and the topic it relates to. All the chapters start by locating the studies within their social and historical context - identifying the concerns that motivated researchers, and the particular perspective that informed their scientific thinking. The studies' methods and findings are then presented. This is followed by a discussion of the studies' impact, before concluding with a consideration of the way in which, from the time that they were conducted, the field has moved beyond the classic studies. The result is a volume which is not only enjoyable and informative to read, but one that should support Developmental Psychology courses at any level.
An introduction to the classic studies in developmental psychology / Alan M. Slater and Paul C. Quinn -- Attachment and early social deprivation : revisiting Harlow's monkey studies / Roger Kobak -- Conditioned emotional reactions : revisiting Watson and Rayner's Little Albert / Thomas H. Ollendick [and others] -- Infants on the edge : beyond the visual cliff / Karen E. Adolph and Kari S. Kretch -- Revisiting Piaget : a perspective from studies of children's problem-solving abilities / David Klahr -- Imitation in infancy : revisiting Meltzoff and Moore's (1977) study / Alan M. Slater -- Object permanence in infancy : revisiting Baillargeon's drawbridge study / Denis Mareschal and Jordy Kaufman -- Children's eyewitness memory and suggestibility : revisiting Ceci and Bruck's (1993) review / Kelly McWilliams [and others] -- How much can we boost IQ? : an updated look at Jensen's (1969) question and answer / Wendy Johnson -- Reading and spelling : revisiting Bradley and Bryant's study / Usha Goswami -- Theory of mind and autism : revisiting Baron-Cohen et al.'s Sally-Anne study / Coralie Chevallier -- Moral development : revisiting Kohlberg's stages / Gail D. Heyman and Kang Lee -- Aggression : revisiting Bandura's Bobo Doll studies / Jennifer E. Lansford -- Language development : revisiting Eimas et al.'s /ba/ and /pa/ study / Richard N. Aslin -- Resilience in children : vintage Rutter and beyond / Ann S. Masten.
Includes bibliographical references and indexes.
Keywords: Developmental psychology; Developmental psychology; Entwicklungspsychologie